City suburbs placing suburbia in a post-suburban world - Mace, Alan (Routledge, 2013)
Suburbs are too often ignored in urban research as the peripheral regions of cities, or else studied in isolation from the city they surround. The phenomenon of the suburb must be explored in relation to its city counterpart - its characteristics, community and culture are unique yet inextricably linked to the city. In City Suburbs, Alan Mace situates the suburb in an increasingly urbanising landscape. Mace investigates suburbs and suburbia in two parts: first, a theoretical analysis of the historical and contemporary literature on the development of the-suburban, area; second, through empirical research in London using the idea of a Bourdieuian housing field; concluding with discussion on the potential for as uburban research methodology. Through a focus on London, the conclusions are used to illustrate the broader theories and research of suburbs which can be applied internationally. Ideal supplementary reading for undergraduate and postgraduate students interested in the development and structure of the city, and those on courses on urban planning, human geography, sociology and urbanism.--Book jacket.